Male Patients With Dilated Cardiomyopathy Exhibiting a Higher Heart Rate Acceleration Capacity or a Lower Deceleration Capacity Are at Higher Risk of Cardiac Death - Yang, Yichen; Wang, Fengyan; Zou, Cao; Dong, Hongkai; Huang, Xingmei; Zhou, Bingyuan; Li, Xun; Yang, Xiangjun (Frontiers in Physiology, 2018)
The effects of dilated cardiomyopathy (DCM) on cardiac autonomic regulation and electrophysiology, and the consequences of such changes, remain unclear. We evaluated the associations between heart rate acceleration capacity (AC) and deceleration capacity (DC), heart structural and functional changes, and cardiac death in 202 healthy controls and 100 DCM patients. The DC was lower and the AC was higher in DCM patients (both males and females). Multivariable, linear, logistic regression analyses revealed that in males, age was positively associated with AC in healthy controls (N=85); the left atrial diameter (LAD) was positively and the left ventricular ejection fraction (LVEF) was negatively associated with AC in DCM patients (N=65); age was negatively associated with DC in healthy controls (N=85); and the LAD was negatively and the LVEF was positively associated with DC in DCM patients (N=65). In females, only age was associated with either AC or DC in healthy controls (N=117). Kaplan–Meier analysis revealed that male DCM patients with greater LADs (>46.5 mm) (long-rank chi-squared value=11.1, P=0.001), an elevated AC (> -4.75 ms) (log-rank chi-squared value=6.8, P=0.009), and a lower DC (< 4.72 ms) (log-rank chi-squared value=9.1, P=0.003) were at higher risk of cardiac death within 60 months of follow-up. In conclusion, in males, DCM significantly affected both the AC and DC; a higher AC or a lower DC increased the risk of cardiac death.